The Effect of Anagram Game on Students’ Vocabulary at the Tenth Grade of Senior High School 4 Palopo - Wahidin Wahidin; Rustan Santaria; Jufriadi Jufriadi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study investigates the impact of the Anagram Game on English language vocabulary acquisition among tenth-grade students at Palopo Public High School 4. Employing a quantitative approach, the research utilizes a quasi-experimental design with two classes: the experimental class (16 students) and the control class (16 students). Data collection involves pre-tests, treatments, and post-tests using a vocabulary test. The collected data are analyzed using the SPSS 20 program. Following hypothesis testing criteria, if the two-tailed significance (p) is less than alpha (a) 0.05, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. The study yields a two-tailed significance value of 0.003, indicating that p < a. This result signifies a significant impact of the Anagram Game on vocabulary acquisition. The research findings support the acceptance of the hypothesis, concluding that there is a notable difference in scores for vocabulary skills between students taught with the Anagram Media and those without. In summary, the researcher concludes that Anagram Media is effective in enhancing students' comprehension of vocabulary skills among tenth-grade students at SMA Negeri 4 Palopo.